High bandwidth performance of newly designed multimode W-type microstructured plastic optical fibers with graded-index core distribution - Ana Simović; Branko Drljača; Milan S. Kovačević; Ljubica Kuzmanović; Alexandar Djordjevich; Konstantinos Aidinis; Changyuan Yu; Xiong Deng; Svetislav Savović (Scientific Reports)
Abstract A new design of multimode W-type (doubly clad) microstructured plastic optical fiber (mPOF) with graded-index (GI) distribution of the core is proposed, along with a methodology for examining transmission along it. The power flow equation’s (PFE) numerical solution yields the transmission properties of the W-type GI mPOF. We have demonstrated that the coupling length L c at which an equilibrium mode distribution (EMD) is reached in W-type GI mPOF is shorter than the length experimentally found for the conventional singly- clad (SC) GI POF. This results from leaky mode losses, which lower the length L c in W-type GI mPOF by lowering the amount of higher guided modes engaged in the coupling process. As a result, the bandwidth of W-type GI mPOF significantly increases. It is noteworthy that, when compared to the experimental bandwidth of commercially available conventional POFs, the bandwidth of the W-type GI mPOF proposed in this work is noticeably higher. Consequently, the bandwidth performance of short-haul communication lines may be significantly improved by using such a designed W-type GI mPOF.